Effects of lactulose on growth, carcass characteristics, faecal microbiota, and blood constituents in broilers - Mohammadi Gheisar, M.; Nyachoti, C. M.; Hancock, Joe D.; Kim, I. H. (My University, 2016)
This study was conducted to determine the effect of supplementing diets with lactulose on growth performance, carcass characteristics, faecal microbiota, and blood constituents. A total of 324 one-day-old Ross 308 mixed-sex broiler chicks with an average initial body weight of 38 g were used in a 35-day growth assay. There were 18 birds/pen and six pens/treatment with food and water available ad libitum. Treatments consisted of a corn-soybean-meal-based diet with 0, 0.25 and 0.5% of lactulose. The results indicated that body weight gain (BWG) was improved (linear effect, P < 0.05) by increasing the concentration of lactulose in the diet from zero to 0.5% while the feed conversion ratio (FCR) decreased (linear effect, P < 0.05) for Days 8 to 21, 21 to 35, and overall (Day 0 to 35). Chickens fed the diet supplemented with 0.5% lactulose showed a higher relative weight of breast meat compared to other groups. Inclusion of lactulose decreased the count of Salmonella and E. coli in excreta of chickens fed diets containing 0.25 or 0.5% lactulose (P < 0.05), but the count of Lactobacillus was not affected. Drip loss percentage was decreased (P < 0.05) on Day 1 by addition of 0.5% lactulose, but there was no effect on meat colour. Blood characteristics were not influenced. Thus, it was concluded that inclusion of lactulose improves growth performance and alters excreta microbial populations with no adverse effect on broilers.
Citation: Mohammadi Gheisar, M., Nyachoti, C. M., Hancock, J. D., & Kim, I. H. (2016). Effects of lactulose on growth, carcass characteristics, faecal microbiota, and blood constituents in broilers. Veterinarni Medicina, 61(2), 90-96. doi:10.17221/8722-VETMED
Keywords: Broiler; Carcass Characteristics; Excreta Microbiota; Growth Performance; Lactulose